STANDARD ANALYSIS OF THE IMPACT OF SOME FISCAL POLICY TOOLS ON THE ECONOMIC PERFORMANCE INDEX IN IRAQ FOR THE PERIOD 2005-2024 - Dr. Abdullah Muhammad Rashid Al-Ramli; Dr. Mohammed Madlool Ibrahim; Mustafa Ibrahim Abdullah (Scholar Express Journals, 2025)
This research aims to examine and assess the impact of fiscal policy tools on Iraq's economic performance by determining the extent to which tax revenues and public spending have an impact on the GDP for the years 2005–2024. The study is noteworthy because one of the most crucial tools that countries use to influence economic activity and achieve stability and progress is fiscal policy. The research used a descriptive and analytical approach in addition to conventional methodologies via the use of simple and multiple linear regression models, and it was based on official data made public by the Iraqi Ministry of Finance, the Central Bank of Iraq, and the International Monetary Fund. The proper statistical analytic techniques were used to evaluate the relationship between fiscal policy variables and GDP
Keywords: Fiscal policy; public spending; tax revenues; economic performance